Analysis of social emotional problems during the PAUD-SD transition period in class 1 of SDN Kamal 1 - Sofiyeh, Sofiyeh; Nurharini, Firdausi; Yuniatari, Yuniatari (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
This research aims to determine social emotional problems during the PAUD-SD transition period in class 1 of SDN Kamal 1 and the challenges and efforts made. The method used in this research is a qualitative descriptive method. The results of the research show that social emotional problems during the transition period from PAUD-SD in class 1 of SDN Kamal 1 are; (1) self-awareness, children cannot yet recognize their own feelings and behavior, recognize their strengths and weaknesses and evaluate themselves, (2) self-management, children cannot control their emotions, (3) social awareness, children cannot understand norms social norms include those that are unfair and do not accept other people's points of view, (4) social interaction skills, children are not yet able to get along with their peers, initiate interactions or communicate with their friends, do not actively listen to other people who are talking, maintain conversations and wait turn, (5) responsible decision making, children can't do it yet analyze situations from multiple points of view, identify possible options, explore the consequences of each option and demonstrate curiosity, honesty, integrity and fairness.